Kajian Naratif: Praktik Konsumsi Jenis Makanan Untuk Peningkatan Kadar Hemoglobin Pada Remaja Putri - Dwika Julian Zahara; Tuti Surtimanah (Sehat MasadaJurnal, 2023)
Anemia is a condition where the red blood cells are below the normal category. The incidence of adolescent girls anemia in 2012 in Indonesia was 75.9%. One way to overcome the incidence of anemia by consuming foods that contain high iron and other nutrients. The purpose of the study was to determine the types of food that could be consumed by adolescent girls in order to increase Hb levels. The research method is literature review. Search articles using Google Scholar and ResearchGate with the keywords (“Hemoglobin Increase” and “Adolescent Girls”). Synthesis of the results using a matrix of summary articles, identification and comparison of themes. The results showed that there was an effect of certain types of food on increasing Hb levels, namely in the form of juices (kurlapa juice, SF+red guava juice, beetroot juice, green bean juice) and other foods (rice flakes+jaggery, dates, eggs, laddu yeast+ Moringa leaf powder + Fe tablets, Moringa leaf powder, tolo bean sticks). Green bean juice is most effective because it contains substances for the formation of red blood cells. The provision of green bean juice which is relatively cheap and easy to manufacture can be widely given to young women.